CXCL12/CXCR4 axis mediates CD8 + T cell overactivation in the progression of viral myocarditis - Li Zhang; Keyu Liu; Xiuyun Duan; Shan Zhou; Hailin Jia; Yingnan You; Bo Han (Journal of Translational Medicine)
Abstract Background Myocarditis is a common inflammatory heart disease in children and young adults, with fulminant myocarditis (FM) being the most severe form due to its rapid onset and high mortality rate. However, the precise pathological immune subsets and molecular change in myocarditis, particularly FM, remain unknown. Methods We performed single-cell RNA sequencing of pediatric peripheral blood mononuclear cells during the acute and recovery phases of FM. A viral myocarditis (MC) mouse model was established using CVB3. Deletion and adoptive transfer of CD8+T cells, as well as blockade of CXCR4, were conducted in vivo. CD8+T cells were sorted and cultivated in vitro, then stimulated with CXCL12 and CXCR4 antagonists to investigate the mechanism of CD8+T cell overactivation. Results CD8+T cells show significant activation, amplification, enhanced cytotoxicity, and increased chemotactic ability in FM. Deletion of CD8+T cells alleviates myocardial injury and improves cardiac function in MC mice, while adoptive transfer of CD8+T cells from MC mice aggravates myocardial inflammation and injury. The transcriptomic analysis reveals elevated CXCR4 expression in CD8+T cells in acute FM. In vitro experiments demonstrate that the CXCL12/CXCR4 axis drives the overactivation and cytotoxicity of CD8+T cells. In vivo treatment with a CXCR4 antagonist effectively reduces CD8+T cell accumulation in the heart, alleviates myocardial inflammation, and improves cardiac function in MC mice. Conclusions These findings provide deeper insights into the immune landscape of pediatric FM, uncovering a novel role of the CXCL12/CXCR4 axis in driving CD8+T cell responses in myocarditis. Furthermore, they highlight the CXCL12/CXCR4 axis as a promising therapeutic target for myocarditis treatment.